Learner Autonomy in EFL Online Classes in Indonesia: Students’ Voices - Rolisda Yosintha; Sukma Shinta Yunianti (Langkawi: Journal of The Association for Arabic and English, 2021)
While learner autonomy has proved to be one of the determinants of successful language learning, little has been scrutinized when implemented in EFL online learning settings.   This study aimed to investigate learner autonomy in English as a Foreign Language (EFL) online classes as viewed from the students’ standpoints. Through a mixed-method approach, the researchers collected data both quantitatively and qualitatively using questionnaires and interviews. As many as 513 students from 8 universities across Indonesia filled out the questionnaires, and 10 of them were interviewed to corroborate the findings. The quantitative data were converted into percentages, while the qualitative ones were analyzed using content analysis by categorizing them into themes, coding, and evaluating to find connections. The findings show that most students (80.5%) had positive attitudes towards their autonomy during English online learning, as indicated in their motivation to be self-reliant. Even so, this positive attitude did not imply satisfactory learning outcomes, for there were only 18.5% of the students who got an A in their English course. To make learner autonomy impact achievement, lecturers could take pedagogical measures, such as encouraging peer-tutoring, selecting interesting and easy-to-use online learning platforms, and implementing the Project-Based Learning model. These findings imply that teachers should be more thoughtful in selecting learning activities and settings that could stimulate the development of learner autonomy.